Application of the leadership model in health services: a systematic review - Siti Aminah; Trias Mahmudiono (AOSIS, 2023)
Introduction: Leadership is a process similar to management in many ways. Leadership involves influence, as does management. Leadership requires working with people who need management as well. Leadership is concerned with the effective attainment of goals, and so is management. Effective leadership of health professionals is very important to strengthen the quality and integration of health services and effective leadership also depends on the approach or leadership style adopted. Objective: The purpose of this study is to determine the leadership model in health services based on the literature review. Materials and Methods: The design used is a literature review, articles were collected using electronic databases such as ScienceDirect, Google Scholar, and PubMed from 2013-2022. The analysis uses journal content analysis. Results: Based on the results of the literature review, it was found that the most widely used leadership model is the transformational leadership model. Discussions: Transformational leadership is a leadership style through a process of increasing aspirations, inspiration, and motivation, having a vision for the future, and being able to identify environmental changes and transform extraordinary changes into an organization so that coordinated members foster a high sense of trust that can encourage to build a solid team. and contribute more to the organization. Conclusions: Leadership is one of the main determinants related to success and failure in an organization. The most frequently used leadership style is transformational leadership.